Effect of Time Temperature History on Coffee Aroma during Roasting with Heat Conduction - Karyadi, Joko Nugroho Wahyu (2009)
The objective of this research is to determine the effect of time temperature history on coffee aroma. Four levels of temperature (160, 180, 200, and 220oC) were used for roasting temperature with heat conduction. The dried mature of coffee beans (12% MC w.b.) was used as samples. About 100 gram of Robusta coffee was subjected on each pan temperatures during 12 minutes. The surface of pan temperature was automatically controlled and the coffee was stirred manually during roasting. During roasting aroma observation was conducted with an own made electronic nose using four gas sensors (TG S880, TGS 826, TGS 825, and TGS 822). Air delivery time is 90 seconds and it is repeated five times. Temperature was measured every 2 minutes with thermo logger. The weight loss and moisture content were determined every 2 minutes. Coffee aroma was measured by two methods; firstly the aroma was measured during roasting, and the second the coffee aroma was measured after cold condition for samples of 0, 2, 4, 6, 8, 10 and 12 minutes. Coffee aroma was determined by sucking the air over the pan and it was delivered to the gas sensors array. Air delivery time is 90 seconds and it is repeated for five times. The result shows that the final moisture content of coffee after 12 minute at roasting temperature (160, 180, 200, and 220oC) are 3.6; 2.6; 1.8 and 1.1%. The surface temperature of 160oC result an unroasted coffee. The appropriate temperature for roasting is about 180 to 220oC. The voltage changes for all sensors were observed for all temperatures. Increasing the voltage indicate the change of aroma during roasting. Decreasing of voltage indicated the roasting has finished. The characteristic of coffee aroma was calculated using principle component analysis (PCA). This pattern recognition system could be used for classification of coffee aroma.